EFEKTIVITAS MEDIA SAKURA (SUSUN HURUF, SUKU KATA, DAN KATA) BERBASIS MULTISENSORI UNTUK MENINGKATKAN KEMAMPUAN MEMBACA BAGI ANAK DISLEKSIA DI SEKOLAH DASAR - Nursara, Siska; Rofiah, Nurul Hidayati (Jurnal Fundadikdas (Fundamental Pendidikan Dasar), 2018)
The purpose of this study was to examine the effectiveness of multisensory-based SAKURA media. The research method used was a single subject type experimental method with the A-B-A research design. The instrument used was a matter of dyslexic children's reading ability test. The subject in this study was a dyslexic child in Sempu Public Elementary School. Data analysis techniques used are descriptive statistics, analysis of conditions, and analysis of conditions. Based on the results of research and discussion, it can be concluded that SAKURA media is effective in increasing the reading ability of GAS subjects. This can be proven by an increase in the percentage of subject achievement at the time of the intervention. In this study, subjects (GAS) got mean levels increasing from 75.2 under baseline 1 (A1) to 88.9 under intervention (B), and 99.3 under baseline 2 (A2). A low percentage of overlap supports this. The percentage overlap between baseline one condition and intervention conditions is 0%, and intervention conditions with baseline 2 are 0%.